Proceedings of the 1st International Conference on Learning Analytics and Knowledge 2011
DOI: 10.1145/2090116.2090131
|View full text |Cite
|
Sign up to set email alerts
|

The value of learning analytics to networked learning on a personal learning environment

Abstract: Abstract. Some might argue that the analytics tools at our disposal are currently mainly used for boring purposes, such as improving processes and making money. In this paper we will try to define learning analytics and their purpose for learning and education. We will ponder on the best possible fit of particular types of research methods and their analysis. Methodological concerns related to the analysis of Big Data collected on online networks as well as ethical and privacy concerns will also be highlighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 4 publications
2
62
0
3
Order By: Relevance
“…This study proposes a multidimensional learning evaluation from an online blended seminar classroom different mode of studying. Learning analytics has shown the various course units that need improvement [2]. This however helps to inform a better course delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study proposes a multidimensional learning evaluation from an online blended seminar classroom different mode of studying. Learning analytics has shown the various course units that need improvement [2]. This however helps to inform a better course delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The data is further analysis for academics and educational online blended system using a statistical package for the social sciences (SPPS) tool. Learning analytics has shown the various course units that need improvement [2], this however helps to inform a better course delivery. The use of learning technology as a catalyst towards enhancing the learning process for learners in educational contexts thus involves an investigation of the learners themselves, the content to which they have engage with in this context, the learning platform environment itself and the components that comprised in this environment.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of data from different elements of online learning has identified that there are patterns of engagement that are reflected in academic outcomes. These include patterns that identify perceived sense of community (Dawson, 2008), participation and social connections (Fournier et al, 2011) disconnected students and student-to-student communication (Macfadyen and Dawson, 2010). Learning analytics data and methods can be employed to identify the potential impact of the socialising efforts of active participation in the online discussion forum on the student's final mark.…”
Section: Review Of the Literature Learning Analyticsmentioning
confidence: 99%
“…In the context of a social learning pedagogy, learning analytics have been used to identify perceived sense of community (Dawson, 2008), participation and social connections (Fournier et al, 2011) and identify disconnected students and patterns of student-to-student communication (Macfadyen and Dawson, 2010). The data gathered can guide the use of limited resources allowing faculty to customise instruction and improve teaching and learning environments (Ferguson, 2012, Johnson et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Log stream data does not provide a complete picture of all learner behaviours; for example, it e xcl udes those forms of engagement with learning that occurs off-line or may not leave a digital trace, such as i n some forms of emotional engagement (Fournier, Kop, & Sitlia, 2011;Veletsianos, Colleer, & Schne i der, 2015). The data are rarely designed for research purposes, and have been found variously to b e too granular or not granular enough for some purposes (Kizilcec, Piech, & Schneider, 2013), or too patchy or incomplete, or too inaccurate, confounded, or corrupted with data unrelated to learning (Dringus, 2012;Greller & Draschler, 2012;Siemens & Long, 2011).…”
Section: Constructing a Measure Of Capability From Log Stream Datamentioning
confidence: 99%